(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Pregnancy is one of the most important events in the life of every woman. Antenatal care is essential for diagnosis of high risk cases and for educating the pregnant women about the physiological changes and process of delivery. By these fear is removed and psychology of pregnant women improved. The main objective of antenatal care is to delivery healthy fetus from a healthy mother. The prevalence of the C-section in India was 8.5% in NFHS-3 while data in NFHS-4 showed that it has increased upto 17.2%. Thus, almost 9% has increased over 10 years. In the present scenario incidence of Caesarean section has been increased. When labour is induced with oxytocin or prostaglandin leads to cervical dystocia, uterine inertia are more evident. Acharyas are explained Navama masa garbhini parcicharya for Sukha prasava or Dhatu vriddhi. Basthi which helps in Vata anulomana and softness Kukshi, Kati and Parshwa pradesha. Aim and objective: To achieve normal vaginal delivery without complication and to know the efficacy of Ayurveda treatment modalities in Sukha prasava. Methodology: Oral administration of Dashamula kashya 20 ml second hourly and Dhanwantaram taila yoni pichu till the full dilatation of cervix. Results: There is reduction in duration of first stage of labor. Conclusion: Dashamula kashaya and Yoni pichu with Dhanwantara taila was effective in progress of labor without complication.